Sweets for my sweet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Ever wondered if dried fruits taste twice as nice when exported? Well, several African companies are happily finding sweet success on the world s markets and are pushing ahead with production. One Togolese firm, Safleg, itself a member of the...